Clinical Relevance of Right Atrial Functional Response to Treatment in Pulmonary Arterial Hypertension - Richter, Manuel J.; Zedler, Daniel; Berliner, Dominik; Douschan, Philipp; Gall, Henning; Ghofrani, Hossein A.; Kimmig, Lucas; Kremer, Nils; Olsson, Karen M.; Brita da Rocha, Bruno; Rosenkranz, Stephan; Seeger, Werner; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Right atrial (RA) function has emerged as an important determinant of outcome in pulmonary arterial hypertension (PAH). However, studies exploring RA function after initiation of specific pulmonary vascular treatment and its association with outcome in patients with incident PAH are lacking. Methods: RA peak longitudinal strain (PLS), passive strain (PS) and peak active contraction strain (PACS) were retrospectively assessed in 56 treatment-naïve patients with PAH at baseline and during follow-up after initiation of specific monotherapy or combination therapy. Patients were grouped according to their individual RA functional response to treatment, based on change from baseline (Δ): worsened (first ∆-tertile), stable (second ∆-tertile), and improved (third ∆-tertile). Spearman’s rho correlation and linear regression analysis were used to determine associations. Time to clinical worsening (defined as deterioration of functional class or 6-minute walking distance, disease-related hospital admission, or death) was measured from the follow-up assessment. The association of RA functional treatment response with time to clinical worsening was assessed using Kaplan–Meier and Cox regression analyses. Results: Median [interquartile range] time to echocardiographic follow-up was 11 [9–12] months. Of the 56 patients, 37 (66%) received specific dual or triple combination therapy. Δ RA PLS during follow-up was significantly associated with changes in key hemodynamic and echocardiographic parameters. The change of pulmonary vascular resistance, right ventricular (RV) end-systolic area and global longitudinal strain were independently associated with Δ RA PLS. The median time to clinical worsening after echocardiographic follow-up was 6 [2–14] months (17 events [30%]). In multivariate Cox regression analysis, worsening of RA PLS was significantly associated with clinical deterioration (hazard ratio: 4.87; 95% confidence interval: 1.26 to 18.76; p = 0.022). Patients with worsened RA PLS had a significantly poorer prognosis than those with stable or improved RA PLS (log-rank p = 0.012). By contrast, PS and PACS did not yield significant prognostic information. Conclusion: Treatment-naïve patients with PAH may show different RA functional response patterns to PAH therapy. These functional patterns are significantly associated with clinically relevant outcome measures. Improvements of RA function are driven by reductions of afterload, RV remodeling, and RV dysfunction.